2022
DOI: 10.1038/s41598-022-05607-y
|View full text |Cite
|
Sign up to set email alerts
|

Inventory reveals wide biodiversity of edible insects in the Eastern Democratic Republic of Congo

Abstract: In response to growing food demand, edible insects are perceived as an opportunity to alleviate food insecurity. With its wide edible insects’ biodiversity, the Democratic Republic of Congo is one of Africa’s most critical entomophagous. This study aimed at giving a first insight on inventory showing diversity, perception, consumption, availability, host plants, harvesting techniques and processing techniques of edible insects in South-Kivu, DRC. It recorded twenty-three edible insects belonging to nine famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…While emerging research has demonstrated the health benefits of edible insects, including antimicrobial, nutritional, and therapeutic properties [ 29 ], few studies have evaluated implementation of an edible insects programs among populations vulnerable to malnutrition. Most research advocating for edible insect consumption are observational studies on traditional practices [ 30 ], including in Madagascar [ 31 ], the Democratic Republic of Congo [ 32 ], and Thailand [ 33 ], or acceptability studies in Western countries without traditions of edible insects [ 34 ]. Acceptability studies in Liberia and Ghana have shown important stakeholders, including caregivers, patients, community leaders, and healthcare professionals, to have favorable opinions towards palm weevil larvae farming as a source of nutrition [ 19 , 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While emerging research has demonstrated the health benefits of edible insects, including antimicrobial, nutritional, and therapeutic properties [ 29 ], few studies have evaluated implementation of an edible insects programs among populations vulnerable to malnutrition. Most research advocating for edible insect consumption are observational studies on traditional practices [ 30 ], including in Madagascar [ 31 ], the Democratic Republic of Congo [ 32 ], and Thailand [ 33 ], or acceptability studies in Western countries without traditions of edible insects [ 34 ]. Acceptability studies in Liberia and Ghana have shown important stakeholders, including caregivers, patients, community leaders, and healthcare professionals, to have favorable opinions towards palm weevil larvae farming as a source of nutrition [ 19 , 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anthropo-entomophagy practices have been increasingly documented worldwide [9,14,[28][29][30][31][32][33][34][35] but less so in the Democratic Republic of Congo (DRC) despite its wide edible insect diversity. A recent study conducted in South-Kivu, in the Fizi, Kabare, Mwenga, and Walungu territories, recorded 23 edible insects [11], but due to ecological, cultural, and dietary habit differences, the results from these territories cannot be extrapolated to Kalehe and Idjwi consumers. There is a need for in-depth research on the diversity of edible insects, the factor influencing their preferences, their seasonal availability, harvesting techniques, and processing techniques for sustainable use, as understanding edible insects' diversity and value chain is critical in promoting edible insects, especially in a context of climate change and ecosystem deforestation, which is currently affecting DRC.…”
Section: Introductionmentioning
confidence: 99%
“…These edible insects are generally consumed as eggs, larvae, pupae, adults, or nymphs [11,12], and most of them are collected from nature [13]. Several species including Imbrasia oyemensis (caterpillar) are consumed as both larvae and pupae [11], and Apis millifera (honey bee) as eggs, larvae, and pupae [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Edible insects remain a sustainable source of income for low-income households across Africa [ 2 , 28 ], with most of the harvesting [ 29 ] and preparation for consumption being conducted by women [ 30 ], for example, the Gonimbrasia belina (mopane worms) ( Figure 1 ). Across southern Africa, the mopane worms trade is estimated to be valued at USD 85 million [ 19 ], with the majority of trading being conducted by women.…”
Section: Introductionmentioning
confidence: 99%